Critical Incidents, Re ective Writing, and Future Teachers’ Professional Identities - Sevilla Morales, Henry; Gamboa Mena, Roy (Revista de Lenguas Modernas, 2017)
A number of recent studies point to the bene ts of critical incidents and re ective writing in the language instruction process. Within this context, this study purports to unveil the role that critical incidents and re ective writing play in the con guration of future EFL teachers’ professional identities. To this end, 30 senior college students enrolled in an English Teaching Major wrote and re ected on critical incidents that have shaped their language learning and teaching of English experiences. Once data had been gathered, the researchers followed Freeman’s (1998) four-stage process for data analysis and interpretation. Findings were later on theorized in light of the research goal and the theory discussed in the theoretical framework. Conclusions are that (1) spaces for re ection should be opened so that positive practices are kept and the negative can be dismantled, (2) re ective writing through critical incidents is an effective way to realize professional and other social identities, and (3) re ective writing through critical incidents is a bridge through which dialogue can be initiated amongst all educational actors. The study vindicates the use of narrative inquiry as a way to explore learner’s affective domain and to understand educational phenomena as embedded within a speci c socio-cultural context. Estudios recientes resaltan la relación entre los incidentes críticos, la escritura re exiva y el aprendizaje de lenguas. Dentro de este contexto, este estudio busca desvelar el papel de los incidentes críticos y la escritura re exiva en la con guración de la identidad profesional de futuros docentes de inglés como lengua extranjera (EFL). Para tal cometido, 30 estudiantes universitarios de cuarto año de una carrera de enseñanza del inglés escribieron y re exionaron sobre incidentes críticos que han forjado sus experiencias de aprendizaje y enseñanza del inglés. Recolectados los datos, los investigadores siguieron el proceso de cuatro etapas para el análisis e interpretación de resultados propuesto por Freeman (1998). Posteriormente, teorizaron sobre los hallazgos a la luz del objetivo de investigación, así como de lo discutido en el marco teórico. Se concluye que (1) se deben abrir espacios de re exión que ayuden a preservar las prácticas docentes positivas y a desechar las negativas; (2) la escritura re exiva mediante incidentes críticos constituye un método e caz para comprender identidades profesionales, así como otras de tipo social; y (3) la escritura re exiva mediante incidentes críticos sirve como medio de diálogo entre los distintos actores del proceso educativo. El estudio vindica el uso de la investigación narrativa biográ ca como método para indagar en el dominio afectivo de los estudiantes, a la vez que llama a comprender todo fenómeno educativo dentro de un marco sociocultural determinado.